2023
DOI: 10.1155/2023/1362417
|View full text |Cite
|
Sign up to set email alerts
|

Energy Optimization-Based Clustering Protocols in Wireless Sensor Networks and Internet of Things-Survey

Abstract: Research on popular themes today is mainly concentrated on cutting-edge home applications made up of Internet of Things gadgets. As its principal means of sensing, wireless sensor networks are a component of the Internet of Things. Tracking and monitoring applications benefit from the use of sensor nodes. Every step in the data collection, processing, and transmission processes carried out by wireless sensor nodes takes energy. Small capacity batteries on the sensor nodes in the networks make charging them fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…[525], [528]- [541] Network Security and Intrusion Detection: security risks including node compromise, tampering, malicious attack, unauthorized access, data breaches, cyber-attacks, and adapting suitable IDS Robust encryption techniques, secure communication protocols, efficient access, formidable security measures and energy-efficient operations.…”
Section: B Data Privacy and Confidentialitymentioning
confidence: 99%
See 1 more Smart Citation
“…[525], [528]- [541] Network Security and Intrusion Detection: security risks including node compromise, tampering, malicious attack, unauthorized access, data breaches, cyber-attacks, and adapting suitable IDS Robust encryption techniques, secure communication protocols, efficient access, formidable security measures and energy-efficient operations.…”
Section: B Data Privacy and Confidentialitymentioning
confidence: 99%
“…However, adapting IDS to suit the specific characteristics and limitations of IoT-WSNs remains a significant challenge. The right balance between formidable security measures and energy-efficient operations is paramount for establishing a secure and reliable IOT-WSNs-based SA architecture [131], [498], [541].…”
Section: Network Security and Intrusion Detectionmentioning
confidence: 99%
“…Additional details regarding the derivation can be found in [16]. In this paper, our focus is on examining a reservation-based MAC (Medium Access Control) protocol known as "reserve-and-go" (RESGO), as introduced in [17]. RESGO operates in the following manner: a source node initially reserves intermediate nodes along a route for the purpose of relaying its packets to the destination.…”
Section: Two-dimensional Poisson Topologymentioning
confidence: 99%
“…The interference power from node j can be written as P int j = αP t (ν j r link ) γ = P r ν j γ [8] The probability that an interfering node will transmit and cause interference depends upon the MAC protocol employed. Considering the RESGO MAC protocol, assuming that each node transmits packets with fixed length L (dimension: [b/pck]), it can be shown that the interference probability is equal to the probability that an interfering node transmits during a vulnerable interval of duration L=Rb [17]. This probability can be written as Assuming that the threshold for bit detection is placed at 0, the bit error probability can be written as…”
Section: Connectivitymentioning
confidence: 99%
“…Wireless sensor networks (WSNs) are an emerging technology that allows the collection and transmission of data from a large number of remote sensors to a central location for analysis [1]. These networks are made up of small [2], low-cost devices [3] called wireless sensors that can be deployed in various environments [4], such as agriculture fields [5], to collect data on various parameters such as temperature [6], humidity [7], soil moisture [8], and light intensity [9]. In the agriculture field, WSNs have the potential to revolutionize the way farms operate by providing real-time data on crop growth and environmental conditions [10].…”
Section: Introductionmentioning
confidence: 99%